Impact of commercial natural gas production on geochemistry and microbiology in a shale-gas reservoir - Kirk, Matthew F.; Martini, Anna M.; Breecker, Daniel O.; Colman, Daniel R.; Takacs-Vesbach, Cristina; Petsch, Steven T. (My University, 2013)
We consider the effect that commercial gas production has had on microbiology and water and gas geochemistry in the northern producing trend of the Antrim Shale, an unconventional gas reservoir in the Michigan Basin, USA. We analyzed gas, water, and microbial biomass samples collected from seven wells in 2009 and compared our findings to the result of analyses performed as early as 1991 on samples collected from the same wells. We also examined production records associated with six wells. Water production has decreased sharply over time and is currently at 0.2 to 14.6% of peak levels. While this has happened, the chemical and isotopic composition of gas and water produced from the wells has shifted. The proportion of CO[subscript 2] has increased by as much as 15 mole% while CH[subscript 4] content has correspondingly decreased. Isotopically, the δ[superscript 13]C and δD values of CH[subscript 4] decreased for most wells by averages of 1.3‰ and 9‰, respectively, while δ[superscript 13]C values of CO[subscript 2] increased for most wells by an average of 1.7‰. Alkalinity in the water from each well decreased by 10 mM on average and SO[subscript 4][superscript 2−] content increased from below 50 μM to over 200 μM on average in water from each well with initial values. Microorganisms most closely related to CO[subscript 2]-reducing methanogens were the most abundant group in archaeal clone libraries and SO[subscript 4][superscript 2−] reducers were the most abundant group in bacterial libraries. In contrast, no SO[subscript 4][superscript 2−] reducers were identified in a nucleic acid-based analysis of a sample collected in 2002 from one of the wells we sampled . Our results show that commercial gas production has not only caused chemical and isotopic changes in water and gas in the Antrim Shale but also an increase in the abundance of SO[subscript 4][superscript 2−]-reducing microorganisms, a change that can ultimately have a negative impact on biogenic CH[subscript 4] formation. Processes that can explain these changes include ongoing biogeochemical reactions, groundwater flow, gas desorption, and open-system degassing.
Keywords: Sulfate reduction; Methanogenesis; Antrim Formation; Michigan Basin; Unconventional natural gas reservoir; Black shale